2015
DOI: 10.4491/eer.2015.051
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of organic contaminants in water by iron-induced oxygen activation: A short review

Abstract: Reduced forms of iron, such as zero-valent ion (ZVI) and ferrous ion (Fe[II]), can activate dissolved oxygen in water into reactive oxidants capable of oxidative water treatment. The corrosion of ZVI (or the oxidation of (Fe [II]) forms a hydrogen peroxide (H2O2) intermediate and the subsequent Fenton reaction generates reactive oxidants such as hydroxyl radical (• OH) and ferryl ion (Fe[IV]). However, the production of reactive oxidants is limited by multiple factors that restrict the electron transfer from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 57 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…Zerovalent iron and copper release ionic iron and copper species, such as Fe­(II), Cu­(I), and Cu­(II), as they are corroded by oxygen (intracellular or extracellular) and cellular components. Reactions – describe the corrosion process of zerovalent iron and copper by oxygen. , Among the ionic iron and copper species, Cu­(I) is known as a strong microbicide, and it has been suggested to be responsible for the bactericidal actions of different copper-based antimicrobial systems. ,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zerovalent iron and copper release ionic iron and copper species, such as Fe­(II), Cu­(I), and Cu­(II), as they are corroded by oxygen (intracellular or extracellular) and cellular components. Reactions – describe the corrosion process of zerovalent iron and copper by oxygen. , Among the ionic iron and copper species, Cu­(I) is known as a strong microbicide, and it has been suggested to be responsible for the bactericidal actions of different copper-based antimicrobial systems. ,, …”
Section: Discussionmentioning
confidence: 99%
“…Iron nanoparticles, particularly nanoparticulate zerovalent iron (nZVI or Fe-NPs), have been reported to exhibit antimicrobial properties. Investigators found that Fe-NPs inactivate Escherichia coli and MS2 coliphage mainly by inducing oxidative damage to the cells and viral particles. Fe-NPs and ferrous ion released from Fe-NPs generate reactive oxidants, such as hydroxyl radical ( • OH) and ferryl ion [Fe­(IV)], via the Fenton­(-like) reactions . Fe-NPs exhibited microbicidal activity superior to that of silver nanoparticles under anoxic conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of dissolved oxygen (DO) will result in the formation of reactive oxygen species (ROS, Eqs. 6.32-34) and ferryl iron Fe(IV)O 2+ (Keenan and Sedlak 2008;Lee 2015), in order to promote oxidative processes. However, the reactive oxidant yield is generally low and does not allow to benefit from Fenton reaction for practical applications, without any modification or use of ligand (Mu et al 2017).…”
Section: History Reactivity and Characterizationmentioning
confidence: 99%
“…When nZVI degrades organic pollutants, the nanoparticles serve as electron donors. The two electrons are transferred to an oxygen molecule to form hydrogen peroxide, which is further reduced to a water molecule [41]. The degradation mechanism of pollutants can be summarized according the following reactions (Eqs.…”
Section: Nanomaterialsmentioning
confidence: 99%